2018
DOI: 10.1002/bdm.2106
|View full text |Cite
|
Sign up to set email alerts
|

Group moral discount: Diffusing blame when judging group members

Abstract: People lie more when they work as a group rather than alone. However, do people suspect and morally evaluate groups and individuals differently when they are suspiciously successful? In four experiments, we examine whether (a) suspiciously successful individuals and groups are judged and punished differently and (b) individual group members are judged differently from the group as one unit. Results suggest that people suspect successful groups and individuals to the same extent. However, group members are less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…One explanation could be that emotions do play a mediating role, but not the emotions we examined, that is, anger, hatred, sadness. Another explanation would be that another process suppressed the mediation through moral emotions, for example, diffusion of responsibility )Bandura, Underwood, & Fromson, 1975; Vainapel, Weisel, Zultan, & Shalvi, 2019). It is possible that participants thought there was a norm of double standard and their change of answer would not matter.…”
Section: Resultsmentioning
confidence: 99%
“…One explanation could be that emotions do play a mediating role, but not the emotions we examined, that is, anger, hatred, sadness. Another explanation would be that another process suppressed the mediation through moral emotions, for example, diffusion of responsibility )Bandura, Underwood, & Fromson, 1975; Vainapel, Weisel, Zultan, & Shalvi, 2019). It is possible that participants thought there was a norm of double standard and their change of answer would not matter.…”
Section: Resultsmentioning
confidence: 99%
“…These may bias second parties to attribute heightened intent and causal responsibility, even for groups, which could mask the diffusion of punishment. Another study about punishing cheaters showed that group violators are considered less dishonest than individual ones, but differences in judgments of deserved punishment were not statistically significant ( p = 0.08) 18 .…”
Section: Introductionmentioning
confidence: 95%
“…More recently, El Zein et al (2020) investigated second-party punishment in fairness-based group games but found no difference between proposed punishment for lone fairness violators compared with collective ones (El Zein et al, 2020). Another study of the punishment of cheaters showed that group actors were considered less dishonest than individual actors, but differences in judgments of deserved punishment were only marginally significant (p = .08; Vainapel et al, 2019).…”
Section: Existing Researchmentioning
confidence: 99%